Dinâmica do fósforo em solo muito argiloso sob diferentes preparos de solo e culturas de inverno - Tiecher, Tales (2011)
The cultivation of plants with different skills of acquisition and absorption of phosphorus (P) under different tillage systems for a long period of time can alter the cycling and distribution of P forms in soil. The aim of this study was to evaluate the dynamics of P in a very clayey soil in the subtropical region, originally covered by Atlantic Forest, under systems of tillage and conventional tillage, with cultivation of different species of winter plants in response to soybeans and corn crops. In 1986 was established the experiment with six winter treatments (blue lupine, hairy vetch, oats, turnip, wheat and fallow) implanted in a Rhodic Hapludox in southern Brazil, under no-tillage system (NT) and conventional tillage system (CT). In October 2009, soil samples were collected at five depths (0-5, 50-10, 10-20, 20-30 and 30-40 cm). The forms of P were determined by chemical fractionation of Hedley, desorption of P by sequential extraction with anion exchange resins, the amount of P stored in soil microbial biomass and activity of the acid phosphatase enzyme. Most of the phosphate applied through fertilizer in rational doses, according to plant needs and soil type, was converted in organic forms by plants and soil microbial biomass, instead of being adsorbed by the soil mineral fraction. The application of phosphate in soil under NT created a strong gradient of P availability in depth, and in soil surface layer promoted an increase of P content in organic and inorganic forms, labile and moderately labile, compared to the CT. Growing plants during the winter period in highly weathered subtropical soil increases the importance of biological reactions in the P cycle, especially in the SPD, where a large amount of vegetable waste is deposited on the soil surface, increasing the content of soil organic P, P content stored in the SMB and acid phosphatase enzyme activity. Growing plants with high biomass production, such as oats, and plants capable of acquiring P from less labile forms, such as the blue lupine, under the NT, increased the content of inorganic labile P in the soil of surface layers, due to the higher amount of P recycled. The same, however, did not occur when the incorporation of crop residues by soil disturbance in the CT, because after being mineralized, P follows the same route of adsorption of P in solution, being retained with strong binding energy, in this system.